2001
DOI: 10.1021/cm011131h
|View full text |Cite
|
Sign up to set email alerts
|

Electroless Addition of Catalytic Pd to SnO2 Nanopowders

Abstract: A new procedure based on the electroless reduction of PdCl2 using Sn(II) as reducing agent is reported to efficiently add a controlled amount of Pd to nanoscaled SnO2 powders. The characterization of these powders using XRD, Raman spectroscopy, XPS, ICP, and TEM is presented and discussed in order to show the feasibility of the proposed catalyst addition mechanism as a useful tool for the improvement of existing catalytic materials for gas sensors. Several palladium salt concentrations and reducing agent ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 32 publications
3
28
2
Order By: Relevance
“…This means that the majority of Pd in the as-prepared composites existed in the form of Pd 0 , indicating that Pd 2+ can be effectively reduced by Sn 2+ in aqueous solution at room temperature. This is expected from the standard electrode potentials of the Pd2+/Pd redox pair (0.951 V vs. the standard hydrogen electrode (SHE)) and that of Sn4+/Sn2+(0.151 V vs. SHE) [36].…”
Section: Characterization Of the Catalystsmentioning
confidence: 78%
“…This means that the majority of Pd in the as-prepared composites existed in the form of Pd 0 , indicating that Pd 2+ can be effectively reduced by Sn 2+ in aqueous solution at room temperature. This is expected from the standard electrode potentials of the Pd2+/Pd redox pair (0.951 V vs. the standard hydrogen electrode (SHE)) and that of Sn4+/Sn2+(0.151 V vs. SHE) [36].…”
Section: Characterization Of the Catalystsmentioning
confidence: 78%
“…Preparation of SnO 2 sols: Hydrated tin oxide as a precursor was precipitated by mixing aqueous solutions of SnCl 4 and NH 4 OH. After washing with deionized water five times coupled with filtration or centrifugation, a designated amount of the gel was suspended in an aqueous ammonia solution (pH 10.5), and subjected to a hydrothermal treatment in an autoclave under 5-10 MPa at 200 • C for 3 h. Finally, a transparent sol suspension of tin oxide (1-3 mass%) was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the sensing properties of tin oxide based materials can be improved by sensitization with noble metals, and in spite of intensive investigation, the sensing mechanism is still not well understood [1]. The main difficulty is that the effect of the promoter material depends on the material preparation procedure, deposition method and post-processing treatment [2][3][4][5][6]. Additionally, it was recognized that the development of new materials, according to more and more demanding market expectations, cannot be limited to phenomenological investigations but has to be completed by systematic, direct spectroscopic measurements (EPR, Mössbauer, IR) [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…7 Previous contributions of our group presented new electrochemical addition methods of metals on SnO 2 that can improve its gas-sensing behaviour. 30,31 As the knowledge of the electronic properties of the semiconductor material and the influence in this properties of the metal addition are fundamental for these applications and given that electrochemistry can provide the ground for this understanding, we have started a characterization of tin oxides in borate buffer solution at pH 7.5 following previous work of our lab in the growth of iron oxide films under electrochemical control. 32,33 The results here presented include the reassignment of the oxidation/ reduction voltammetric peaks and, although both techniques might lead to different films as, for example, cyclic voltammetry deals with transient conditions while impedance spectroscopy as here employed looks at stationary conditions, we try to give a brief sketch of the correlation of voltammetric with impedance data.…”
Section: Introductionmentioning
confidence: 99%